Community Responses to Water Quality Decline in the Lake Mendota Watershed - Matthews, Weston; Gunderson, Eric; Gottwig, Quincy; Caple, Scott (My University, 2014)
Land use and land cover (LULC) are critical factors in determining the water quality of surrounding water bodies. Although the mechanisms are different, both urban and agricultural LULC increase the quantity of runoff directly entering nearby hydrological systems as well as increase the phosphorus, nitrogen and chloride content of the runoff. Lake Mendota in Madison, Wisconsin receives runoff from both urban and agricultural LULC, accelerating lake eutrophication and severely degrading its water quality, evoking a response from the community. To understand this response, researchers analyzed archival photos, conducted interviews with the major stakeholders and collected surveys on the knowledge and engagement in best management practices (BMP's) of residents on the lake. Their findings highlight the long history of LULC around Lake Mendota and the currently disbanded efforts to improve the lake's quality, evident in the public's low awareness of water quality issues and the major stakeholders segregated efforts. All of the stakeholders turn to the emerging nonprofit sector to consolidate efforts and increase communal outreach to create one common coalition working towards improving Lake Mendota?s water quality.
Includes Illustrations, Photographs, Maps, Charts, Appendices and Bibliography.
Keywords: Community response; Runoff; Water Quality; Lake Mendota Watershed